Quality of Work Life in Nursing Staff of Private and Government Hospitals - Dewan, Rakhee (Gyan Management Journal, 2019)
Quality Work Life is a multidimensional concept, and is a way of reasoning about people, work and the  organization. It seems that the relationship between Quality of work life and the degree of the nurse's  involvement in their work is a critical factor in achieving higher levels of quality of care delivery. In  spite of the plethora of research on the subject, the efforts on the part of researchers to identify the  factors of quality of work life in the Indian context have not been encouraging. In this study an attempt  has been made to examine the quality of work life of Registered Nurses in private and public hospitals.  The findings reveal that there are significant differences between nurses in private and public hospitals  on Quality of work life dimensions.
Keywords: nurses; quality of work life; autonomy; adequate and fair compensation